Stavropol Regional Psychiatric Hospital: memory of the past — a ladder to the future - V. B. Yarovitskiy; K. A. Kajdash (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In 2023, 80 years have passed since the liberation of Stavropol from the Nazi invaders. The staff and patients of the psychiatric hospital were subjected to the horrors of the fascist regime. 660 patients and 30 employees of the Stavropol Psychiatric Hospital died in the gas chambers. The hospital honors the memory and does its best to preserve the story of people selflessly fulfilling their duty in difficult times for her and the whole country.The purpose of the study. In honor of the anniversary memorable date, the authors of the article want to tell about the history of the Stavropol Regional Psychiatric Hospital in chronological order from the day of its foundation to the present day.Materials and methods: a systematic analysis of scientific literature, archival data of the hospital was carried out, the A.J. Dorsht foundation, stored in the Museum of History of Stavropol State Medical University, was used.Results and discussion. The authors tell about the life of the hospital in different historical periods of our country. Special attention is paid to the period of the Great Patriotic War. It tells about the horrors that the hospital experienced during the German occupation, about the victims among patients and employees whose lives were claimed by the Great Patriotic War. The period of leadership of the outstanding chief physician, man and teacher, Adolf Yakovlevich Dorsht, is described with great respect and recognition.The article summarizes the history of the development of modern psychiatric services in the Stavropol Territory, the prevention of suicidal behavior among adolescents, the provision of psychiatric care to the population during a pandemic and a special military operation.Conclusion. Having survived many trials in its lifetime, at present the Stavropol Regional Psychiatric Hospital has been awarded numerous awards for asceticism in the field of mental health and is the largest in the North Caucasus.